Recombinant protein expression in microbial systems - German L. Rosano (Frontiers Research Topics, 2014)
With the advent of recombinant DNA technology, expressing heterologous proteins in microorganisms rapidly became the method of choice for their production at laboratory and industrial scale. Bacteria, yeasts and other hosts can be grown to high biomass levels efficiently and inexpensively. Obtaining high yields of recombinant proteins from this material was only feasible thanks to constant research on microbial genetics and physiology that led to novel strains, plasmids and cultivation strategies. Despite the spectacular expansion of the field, there is still much room for progress. Improving the levels of expression and the solubility of a recombinant protein can be quite challenging. Accumulation of the product in the cell can lead to stress responses which affect cell growth. Buildup of insoluble and biologically inactive aggregates (inclusion bodies) lowers the yield of production. This is particularly true for obtaining membrane proteins or high-molecular weight and multi-domain proteins. Also, obtaining eukaryotic proteins in a prokaryotic background (for example, plant or animal proteins in bacteria) results in a product that lack post-translational modifications, often required for functionality. Changing to a eukaryotic host (yeasts or filamentous fungi) may not be a proper solution since the pattern of sugar modifications is different than in higher eukaryotes. Still, many advances in the last couple of decades have provided to researchers a wide variety of strategies to maximize the production of their recombinant protein of choice. Everything starts with the careful selection of the host. Be it bacteria or yeast, a broad list of strains is available for overcoming codon use bias, incorrect disulfide bond formation, protein toxicity and lack of post-translational modifications. Also, a huge catalog of plasmids allows choosing for different fusion partners for improving solubility, protein secretion, chaperone co-expression, antibiotic resistance and promoter strength. Next, controlling culture conditions like temperature, inducer and media composition can bolster recombinant protein production. With this Research Topic, we aim to provide an encyclopedic account of the existing approaches to the expression of recombinant proteins in microorganisms, highlight recent discoveries and analyze the future prospects of this exciting and ever-growing field.